Sistemas bidimensionais à base de silício: um estudo ab initio - Vargas, Douglas Willian Duarte de (2023)
Using density functional theory (DFT) calculations we investigated silicon-based two-dimensional systems, where two silicene phases were considered: the low-buckled (LB) silicene and the dumbbell-like (DB) silicene. First, the structural and electronic properties of a heterogeneous van der Waals (vdW) structure consisting of LB silicene and NiI2 single layers were studied. We observed an interaction between the two layers with a net charge transfer from the ferromagnetic semiconductor NiI2 to LB silicene, breaking the inversion symmetry of the LB silicene structure. However, the charges flow in opposite directions for the two spin channels, which leads to a vdW heterostructure with a spin-polarized band gap between the and ★ states. The band gap can be tuned by controlling the vertical distance between the layers. The features showed by this vdW heterostructure are new, and we believe that silicene on a NiI2 layer can be used to construct heterostructures with appropriate properties to be used in nanodevices where the control of the spin-dependent carrier mobility is necessary and this vdW heterostructure can be incorporated into silicon-based electronics. Second, single layers of hexagonal boron nitride (h-BN) and silicene are brought together to form h-BN/(LB or DB) silicene van der Waals (vdW) heterostructures. The effects of an external electric field and compressive strain on the structural and electronic properties were systematically studied through first-principles calculations. The systems show exciting new properties as compared to the isolated layers, such as a tunable band gap that depends on the interlayer distance and is ruled by the charge transfer and orbital hybridization between h-BN and silicene, especially in the case of LB silicene. The electric field also increases the band gap in h-BN/DB silicene and causes an asymmetric charge rearrangement in h-BN/LB silicene. Remarkably, we found a great potential for h-BN layers to functionalize as a substrate for silicene, enhancing both the strain and electric field effects on its electronic properties. These results provide a more detailed understanding of h-BN/silicene 2D-based materials, highlighting promising possibilities in low-dimensional electronics. Third, we investigate the use of DB silicene as an anode material for Li-ion batteries (LiBs). The energetically most stable geometries for Li adsorption on DB silicene were investigated, and the energy barriers for Li-ion diffusion among the possible stable adsorption sites were calculated. We found that DB silicene can be lithiated up to a ratio of 1.05 Li per Si atom, resulting in a high storage capacity of 1002 mAhg−¹ and an average open-circuit potential of 0.38 V, which makes DB silicene suitable for applications as an anode in LiBs. The energy barrier for Li-ion diffusion was calculated to be as low as 0.19 eV, suggesting that the Li ions can easily diffuse on the entire DB silicene surface, decreasing the time for the charge/discharge process of the LiBs. Our detailed investigations show that DB silicone has characteristic features suitable for application in high-performance LiBs. In summary, these three works contributions serve to elucidate the properties of Si 2D and its possible applications in electronic devices.